2000
DOI: 10.1088/0954-898x_11_2_303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the elastic net model applied to the formation of ocular dominance and orientation columns

Abstract: The development and structure of orientation (OR) and ocular dominance (OD) maps in the primary visual cortex of cats and monkeys can be modelled using the elastic net algorithm, which attempts to find an 'optimal' cortical representation of the input features. Here we analyse this behaviour in terms of parameters of the feature space. We derive expressions for the OR periodicity, and the first bifurcation point as a function of the annealing parameter using the methods of Durbin et al (Durbin R, Szeliski R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, for all stationary solutions the regions of high gradient in the orientation map coincide with low gradient regions (the folds of the grid) in the retinotopic map. This is precisely what is generally expected from a dimension-reducing mapping [21,62,63,92]. In the following section, we will investigate which of these solutions become optimal depending on the two parameters σ/Λ and η r that parametrize the model.…”
Section: Coupled Essentially Complex N-planformsmentioning
confidence: 69%
See 2 more Smart Citations
“…However, for all stationary solutions the regions of high gradient in the orientation map coincide with low gradient regions (the folds of the grid) in the retinotopic map. This is precisely what is generally expected from a dimension-reducing mapping [21,62,63,92]. In the following section, we will investigate which of these solutions become optimal depending on the two parameters σ/Λ and η r that parametrize the model.…”
Section: Coupled Essentially Complex N-planformsmentioning
confidence: 69%
“…From prior work, the coverage continuity compromise appears to be a promising candidate for a principle to explain visual cortical functional architecture. Firstly, many studies have reported good qualitative agreement between the layout of numerically obtained dimension reducing maps and experimental observations [19,21,42,[55][56][57][59][60][61][62][63][64][65][66][67][68][69][70][71]. Secondly, geometric relationships between the representations of different visual features such as orientation, spatial frequency and ocular dominance have been reproduced by dimension reduction models [25, 56, 63-65, 68, 72, 73].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many optimization models of the form presented in Eq. (4) have been studied [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The concrete dynamics in Eq.…”
Section: A Dynamical Systems Approachmentioning
confidence: 99%
“…In the primary visual cortex of primates and carnivores, functional architecture can be characterized by maps of various stimulus features such as orientation preference (OP), ocular dominance (OD), spatial frequency, or direction preference . Many attempts have been made to explain and understand the spatial organization of these maps as optima of specific energy functionals the brain minimizes either during development or on evolutionary timescales [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In part (I) of this study we presented an analytical approach to study the coordinated optimization of interacting pairs of visual cortical maps where maps are described by real and complex valued order parameter fields [39] .…”
Section: Introductionmentioning
confidence: 99%